Recommendations for crime scene investigation (Academic Journal of Internal Affairs, 2012)
The author focuses on new methods of criminal tactics concerning inter alia the collection, securing and packaging of the evidence, and features of the crime scene investigation record.
Keywords: site inspection; tactical recommendations; Pál Déri